Effect of Levosimendan on Low Cardiac Output Syndrome After Pericardiectomy - Fang L; Zhu P; Yu G; Lv W; Hu J (Therapeutics and Clinical Risk Management)
Likui Fang,1,2 Pengfei Zhu,2 Guocan Yu,2 Wang Lv,1 Jian Hu1 1Department of Thoracic Surgery, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310003, People’s Republic of China; 2Department of Thoracic Surgery, Hangzhou Red Cross Hospital, Hangzhou, 310003, People’s Republic of ChinaCorrespondence: Jian Hu, Department of Thoracic Surgery, The First Affiliated Hospital, Zhejiang University School of Medicine, 79 Qingchun Road, Hangzhou, 310003, People’s Republic of China, Email dr_hujian@zju.edu.cnBackground: Low cardiac output syndrome (LCOS) after pericardiectomy is associated with high morbidity and mortality. This study aimed to assess the effect of levosimendan on postoperative LCOS in the patients with constrictive pericarditis.Methods: Patients were retrospectively enrolled, and those receiving the treatment of levosimendan were assigned in the LEVO (+) group, and others were in the LEVO (-) group. Postoperative outcomes including durations of intubation, vasoactive agents using, ICU stay, hospital stay and mortality were compared between the two groups.Results: A total of 32 patients were eligible for analysis, 19 of whom were in the LEVO (+) group, and 13 of whom were in the LEVO (-) group. The LEVO (+) group was associated with shorter postoperative duration of intubation (P < 0.001), vasopressor using (P = 0.006), ICU stay (P = 0.001) and hospital stay (P = 0.042), and less incidence of acute liver or kidney injury (P = 0.046). There were no significant differences in 30-day mortality and 1-year mortality between the LEVO (+) group and the LEVO (-) group. The prevalence of adverse events in the LEVO (+) group was acceptable.Conclusion: Levosimendan could be administered in the patients with constrictive pericarditis developing LCOS after pericardiectomy to enhanced postoperative recovery.Keywords: levosimendan, low cardiac output syndrome, constrictive pericarditis, pericardiectomy